New Solution of Psycho-physiological Problem. / Nueva solución de un problema psico-fisiológico - Datskovsky, Israel V. M.; Bocheliuk, Vitalii I.; Nagymzhanov, Azamat K.; Turebayeva, Shynar M.; Nechyporenko, Valentyna V.; Pozdnyakova, Olena L. (Utopía y Praxis Latinoamericana, 1970)
ABSTRACT Three currently known versions of the formulation of a psycho-physiological problem are presented in the introduction. In the second part of the article, facts, known for today, which contradicted at least one of the accepted statements of the psycho-physiological problem were considered, and the sum of these facts contradicts all three initial versions of the statement of this problem. In the third, main part of the article, with respect to already existing, a different view of author on a possible solution of a psycho-physiological problem is given.RESUMEN En la introducción se presentan tres versiones conocidas de la formulación de un problema psico-fisiológico. En la segunda parte del artículo, hechos, conocidos por hoy, que contradijeron por lo menos una de las declaraciones aceptadas del problema psico-fisiológico fueron consideradas, y la suma de estos hechos contradice las tres versiones iniciales de la declaración de este problema. En la tercera parte, principal del artículo, con respecto a lo ya existente, se ofrece una visión diferente de los autores sobre una posible solución de un problema psico-fisiológico.